Análisis de la distribución de esfuerzos en diferentes elementos de retención intrarradicular prefabricados (2008)
ABSTRACT: The three-dimensional (3D) finite element analysis (FEA) was used to analyze the stress distribution in a maxillary central incisor, restored with prefabricated intrarradicular posts. Methods: the model of the dowel-restored tooth used involved dentin, periodontal ligament, cortical and trabecular bone, gingiva, metal-ceramic crown, resin cement and gutta-percha. The dowels were made of titanium alloy, glass fiber and carbon fiber. The dowel was cemented with resin luting agents. The analysis of stress distribution was performed by mean of the use of Algor software. The variables included their modulus of elasticity and Poisson`s ratio for all the components in the model. A load of 200 N was applied to the palatal surface of the crown at an angle of 45 degrees in relation to the longitudinal axis in order to calculate the stress distribution of the restored structure. Results: the results behaved differently depending on the intraradicular element used for retention of the crown. When the modulus of elasticity was higher in the intraradicular retention element, the stress distribution was observed to be higher in it, but it decreased in dentin. Conclusions: within the limitations of the study, it was found that increasing the modulus of elasticity in the dowel decreases the stress in dentin.